Experimental and numerical investigation on mechanical properties and fracture mechanisms of deep marble under triaxial compression - Zanmin Xiong; Dongsheng Chen; Bei Jia; Xiaobo Su (Scientific Reports)
Abstract To investigate the evolution mechanism of rock mechanical properties under high-stress conditions, marble samples from deep underground were selected for a series of triaxial compression tests, microscopic fracture surface scanning, and discrete element numerical simulations. The results indicate that significant changes in the mechanical properties of marble occur when the confining pressure exceeds 30 MPa. Under low confining pressure conditions, the stress-strain curve of the rock exhibits relatively weak post-peak deformation capacity. As the confining pressure increases, the peak strength of the rock increases significantly, while the elastic modulus remains relatively stable. The rock exhibits low cohesion and high internal friction angle. Under high confining pressure conditions, the stress-strain curve demonstrates more ideal plastic deformation characteristics. As the confining pressure increases, the increase in peak strength becomes less pronounced, while the elastic modulus rises. The rock exhibits high cohesion and low internal friction angle. Analysis of the fracture surface morphology shows that under high confining pressure, the failure mechanism of the rock gradually shifts from primarily grain boundary cracking to predominantly transgranular fracture. The microscopic differences in the internal fracture mechanism of the rock are the key factors driving the evolution of its mechanical properties.